2015
DOI: 10.1177/0093650215573961
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial and Social Network Dimensions of Mobile Communication

Abstract: Studies have shown that ethnic segregation is conducive to social segregation. With the advent of information and communication technologies, mobile communication can support non-local social interactions and reconfigure the network composition of ethnic groups. This study focused on the similarities and differences between ethnonational groups in the structure of their cell phone communications. Data for this study include a sample of 9,099 business customers' mobile phone calls from an Israeli mobile operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Second, Mesch (2012) proposed and found evidence for his Social Diversification Hypothesis, which posits that minority (or disadvantaged) groups use the Internet primarily as a method to expand their social capital and meet new people whereas majority (or advantaged) groups use the Internet to maintain their social relationships (Arie and Mesch 2016). Indeed, research has shown that disadvantaged youth (in terms of ethnicity or education) are more likely to have weaker connections with their online contacts than advantaged youth (Gonzalez 2017).…”
Section: Ethnicity and Cyber-behaviorsmentioning
confidence: 99%
“…Second, Mesch (2012) proposed and found evidence for his Social Diversification Hypothesis, which posits that minority (or disadvantaged) groups use the Internet primarily as a method to expand their social capital and meet new people whereas majority (or advantaged) groups use the Internet to maintain their social relationships (Arie and Mesch 2016). Indeed, research has shown that disadvantaged youth (in terms of ethnicity or education) are more likely to have weaker connections with their online contacts than advantaged youth (Gonzalez 2017).…”
Section: Ethnicity and Cyber-behaviorsmentioning
confidence: 99%
“…The depth of Figure 1 recognizes the social embedding of these different functionalities (depth of cube). Following the social stratification hypothesis, the adoption of technology reflects patterns of existing inequalities in society [27] and follow technology appropriation theory [12], we go beyond a binary adoption variable [28]. We track the more fine-tuned scalar variables of communication duration (extensity of media consumption), and communication frequency (intensity of media consumption) (e.g., [29]).…”
Section: Polymodal Media Taxonomy Of Mobile Appsmentioning
confidence: 99%